An investigation into the use of a commonly available fabric dye as a routine stain for tissue samples to be used as a first line, low cost, diagnostic adjunct for the diagnosis of anaphylactic death at autopsy, in a resource-challenged environment - Burgers, Peter (Division of Forensic Medicine and Toxicology, 2016)
A retrospective study of deaths attributable to anaphylaxis at the Salt River Forensic Pathology Laboratory was undertaken, with a view to determine if eosinophilia was present in tissue samples of the spleen, in accordance with previously published research. Suitable cases of non-anaphylactic death were used as controls. Use was made of two commonly available fabric dyes as alternative stains to the traditional Haematoxylin -Eosin ["H&E"].